2022
DOI: 10.1021/acsami.2c07796
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Layer Number-Dependent Heat Transport across Nickel/Graphene/Nickel Interfaces

Abstract: As a typical two-dimensional material, graphene (Gr) has shown great potential to be used in thermal management applications due to its ultrahigh in-plane thermal conductivity (k). However, low interface thermal conductance (ITC) between Gr and metals to a large extent limits the effective heat dissipation in Gr-based devices. Therefore, having a deep understanding on heat transport at Gr–metal interfaces is essential. Because of the semimetallic nature of Gr, electrons would possibly play a role in the heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Time-domain thermoreflectance (TDTR), a technique with ultrahigh temporal and spatial resolutions, has been widely applied to measure the thermal properties of both bulk materials and nanostructured materials. , Meanwhile, TDTR is a nondestructive and noncontact pump–probe technique to study heat transport across heterogeneous interfaces, merely by depositing a metal transducer layer on the target material surface. Particularly, assisted by the equipped high-resolution optical microscopy, TDTR can ensure precise testing locations. , In addition, by combining the interface microstructure and measured thermal boundary conductance ( G ), the single effect of interface characteristics on electron and phonon scattering as well as their coupling behaviors can be analyzed. For instance, for widely studied heat transport across metal/nonmetal interfaces, a large number of studies have demonstrated that electron–phonon coupling at the metal side (the first heat transport pathway) is closely related to the metal orientation and defects near the interface, , and thermal resistance generated in this pathway ( R 1 ) intrinsically is determined by relaxation time (τ) of electrons and phonons. Following this process, the phonon–phonon coupling (the second heat transport pathway) between metal and nonmetal happens, and this coupling process is mainly influenced by defects at the interface, interface orientation, interface compositions, and interfacial bonding .…”
Section: Introductionmentioning
confidence: 99%
“…Time-domain thermoreflectance (TDTR), a technique with ultrahigh temporal and spatial resolutions, has been widely applied to measure the thermal properties of both bulk materials and nanostructured materials. , Meanwhile, TDTR is a nondestructive and noncontact pump–probe technique to study heat transport across heterogeneous interfaces, merely by depositing a metal transducer layer on the target material surface. Particularly, assisted by the equipped high-resolution optical microscopy, TDTR can ensure precise testing locations. , In addition, by combining the interface microstructure and measured thermal boundary conductance ( G ), the single effect of interface characteristics on electron and phonon scattering as well as their coupling behaviors can be analyzed. For instance, for widely studied heat transport across metal/nonmetal interfaces, a large number of studies have demonstrated that electron–phonon coupling at the metal side (the first heat transport pathway) is closely related to the metal orientation and defects near the interface, , and thermal resistance generated in this pathway ( R 1 ) intrinsically is determined by relaxation time (τ) of electrons and phonons. Following this process, the phonon–phonon coupling (the second heat transport pathway) between metal and nonmetal happens, and this coupling process is mainly influenced by defects at the interface, interface orientation, interface compositions, and interfacial bonding .…”
Section: Introductionmentioning
confidence: 99%